Cilliers, Johan Universiteit Stellenbosch Die optiek van homiletiek: Prediking as om-raming van perspektief - Cilliers, Johan (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This article explores the notion of preaching as a form of perception, in particular as pertaining to viewing life through the lenses of Scriptures. The aesthetical concept of “reframing” is utilised to argue that preaching as perception intends behavioral change of a second order (as opposed to first order, i.e. superficial change). Three aesthetical examples are introduced to illustrate this art of reframing, namely works by Duchamp, Zapiro, and Grünewald. The conclusion is that reframing offers a unique option to preach the foolishness of the gospel, in contrast to the wisdom of the world.